2020
DOI: 10.1111/cdoe.12575
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and decomposing socioeconomic‐related inequality in the use of oral health services among Chinese adults

Abstract: Objectives: This study aimed to measure socioeconomic-related inequality and horizontal inequity in the use of oral health services and decompose this inequality among adults of different age groups in China. Methods: In total, 10 973 adults (3669 aged 35-44 years, 3767 aged 55-64 years and 3537 aged 65-74 years) who participated in the 4th National Oral Health Survey (2015-2016) in China were included. Concentration curves and the Erreygerscorrected concentration index (EI) were employed to measure socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The copyright holder for this this version posted August 6, 2021. ; https://doi.org/10.1101/2021.08.02.21261259 doi: medRxiv preprint been carried out at one point in time, or on selected groups of the population, for example in samples of young adults or elderly people. [23][24][25][26][27][28][29][30][31][32] The main finding from this study is that inequalities in use of dental services according to income have decreased over time. This is an interesting result, considering that there is no public or private insurance for dental services in Norway.…”
Section: Discussionmentioning
confidence: 68%
“…The copyright holder for this this version posted August 6, 2021. ; https://doi.org/10.1101/2021.08.02.21261259 doi: medRxiv preprint been carried out at one point in time, or on selected groups of the population, for example in samples of young adults or elderly people. [23][24][25][26][27][28][29][30][31][32] The main finding from this study is that inequalities in use of dental services according to income have decreased over time. This is an interesting result, considering that there is no public or private insurance for dental services in Norway.…”
Section: Discussionmentioning
confidence: 68%
“…14 According to previous studies, dental service utilization among Chinese preschool children may be influenced by caregiver education background, socioeconomic status, perception of their children's oral health status, dental insurance dental fear and demographic factors. 16 Although some studies have found socioeconomic-related inequalities in dental service utilization among adults in China, [17][18][19] the evidence related to inequality in children's dental service utilization is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration index (CI), enjoying increasing popularity, has been used to quantify and measure inequality in dental care service utilization, represent inequality visually by means of the concentration curve and identify the factors contributing to inequality in previous studies. 19,[22][23][24] Inequality in dental care utilization among Chinese adults has been measured in previous studies by means of CI. [17][18][19] However, evidence related to inequality in dental care indicating that dental care utilization in children aged 3-5 years was concentrated in those who were better off.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tselmuun Chinzorig [ 13 ] reported inequalities in caries experience among Mongolian children. Mengru Xu [ 14 ] measured and decomposed socioeconomic-related inequality in the use of oral health services among Chinese adults and found that oral health care service utilization was disproportionately concentrated among better-off Chinese adults. These studies focused either on a single aspect of oral disease or on oral health care service utilization.…”
Section: Introductionmentioning
confidence: 99%